(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
The present work consists of carrying out a case study with sixteen students from the CP Guimarán-Valle (Asturias) between the ages of three and five. The aim is to analyse possible differences in the cognitive and epistemological development of mathematical knowledge according to age. To this end, two activities corresponding to the fields of mathematical knowledge were designed: the field of logical-mathematical knowledge and the field of numerical knowledge. The design of the activities has been developed from the theoretical aspects of the Mathematics Teacher’s Specialised Knowledge (MTSK) model.